A REPORT ON THE INFORMAL MEETING “NOTIZIE DAL FRONTE” (NEWS FROM THE “FRONTE”) HELD AT THE DEPARTMENT OF EARTH SCIENCES IN BOLOGNA MAY 7, 2012 - Negri, Alessandra; Vai, Gian Battista; Amorosi, Alessandro; Antonioli, Fabrizio; Bertini, Adele; Marabini, Stefano; Mastronuzzi, Giuseppe (Alpine and Mediterranean Quaternary, 2013)
Here we shortly report the result of an informal meeting held in Bologna under the auspices of AIQUA to promote the study of an Italian section near Taranto (Italy) showing interesting features and potentially useful as Upper Pleistocene GSSP.